2004
DOI: 10.1017/s1138741600004741
|View full text |Cite
|
Sign up to set email alerts
|

Psychological problems and associated factors at 6 years of age: Differences between sexes

Abstract: In a non-clinical group of 130 children (65 boys and 65 girls), we evaluated the relationships between psychological problems using the Child Behavior Checklist (CBCL) reported by parents, the Inattention Overactivity With Aggression (IOWA) scale reported by teachers, individual factors (Intellectual quotient [IQ], temperament and heart rate) and environmental factors (stress events, mother's profession and being or not being an only child). We found no differences between the sexes in the prevalence of total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
(46 reference statements)
1
7
0
1
Order By: Relevance
“…On the other hand, unlike Broekman et al (32), we found no association between higher birth weight and better IQ. However, the relation that we found between psychological problems and IQ supports the data reported by Delobel-Ayoub et al (3) in preterm children or by Esparó et al (33) in term children. We found no association between neonatal behaviour and performance IQ, so we decided to carry out regression models for each performance scale subtest.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…On the other hand, unlike Broekman et al (32), we found no association between higher birth weight and better IQ. However, the relation that we found between psychological problems and IQ supports the data reported by Delobel-Ayoub et al (3) in preterm children or by Esparó et al (33) in term children. We found no association between neonatal behaviour and performance IQ, so we decided to carry out regression models for each performance scale subtest.…”
Section: Discussionsupporting
confidence: 93%
“…(3) in preterm children or by Esparó et al. (33) in term children. We found no association between neonatal behaviour and performance IQ, so we decided to carry out regression models for each performance scale subtest.…”
Section: Discussionmentioning
confidence: 99%
“…Otros estudios han analizado las relaciones entre funcionamiento motor y nivel cognitivo, encontrando correlaciones significativas directas entre algunas funciones intelectuales y factores psicomotores específicos; igualmente, algunas investigaciones han puesto de relieve la existencia de correlaciones entre inteligencia y conducta social, existiendo relaciones significativas positivas de las dificultades para el aprendizaje y para la comunicación. Así mismo, se ha encontrado que niños con adecuada adaptación social tienen buen desempeño en madurez intelectual global, verbal y no verbal, mostrándose emocionalmente estables, perseverantes y respetuosos con las normas, autocontrolables, confiados y seguros de sí mismos, de allí que se determine que el desarrollo cognitivo, como variable importante en el desempeño motor, se constituya en una variable mediadora en la conducta social (39)(40)(41). Un estudio de Garaigordobil y Amigo determinó que la inteligencia no verbal, la cual implica aspectos psicomotores, correlaciona significativa y positivamente con pensamiento manipulativo (r = 0,27 y p = 0,05), hiperactividad (r = 0,29 y p = 0,05), depresión (r = 0,31 y p = 0,01), somatización (r = -0,25 y p = 0,05), agresividad (r = -0,33 y p = 0,01), exteriorización de problemas (r = -0,32 y p = 0,01) y síntomas comportamentales (r = -0,35 y p = 0,001) (42).…”
Section: Discussionunclassified
“…In this case, the high motor cluster scores could be related to the behavioural characteristics of high motor activity. High motor activity is a trait of difficult [23] or undercontrolled [24] temperament, which is associated with [21], or a precursor of [25], externalizing problems. The early detection of externalizing problems is important because these problems are very prevalent in childhood and adolescence, and can have serious consequences for social, personal and family relations.…”
Section: Discussionmentioning
confidence: 99%
“…The regulation cluster score ( p < 0.01) decreased significantly with age. Descriptive data of the CBCL and IOWA mean scores were reported in Esparó et al [21].…”
Section: Comparison Between Nbas Cluster Scores and Cbcl Dimensionsmentioning
confidence: 99%